En el XXV aniversario de la muerte del teólogo Yves Congar (1904-1995) - Somavilla Rodríguez, Enrique (Estudio agustiniano, 2021)
Life of P. Yves Marie-Joseph Congar, OP, it was from the beginning a set of continual startles. An intellectual man, a committed christian, a self-sacrificing and obedient religious, a brilliant theologian, a fleeting cardinal. The long life of Yves Marie-Joseph Congar, OP, it always happened in a very agitated way, after a series of exiles that they marked deeply its existence: Jerusalem, Rome and Cambridge. His combat in favor of the Nouvelle Théologie, I was worth the troubles from his superiors from the Pope, the Roman Curia, the Sacred Congregation of the Holy Office, the Master Generals of the Order of Preachers, OP and your own religious community. He lived from a committed faith, sincere and unshakable in Jesus Christ. He suffered from jail and the German concentration camps. He was a staunch defender of ecclesiology of the People of God, of the vocation of the Laymen and from Ecumenism.